Applicability of ribosome engineering to vitamin B12 production by Propionibacterium shermanii. Issue 8 (3rd August 2017) - Tanaka, Yukinori; Kasahara, Ken; Izawa, Masumi; Ochi, Kozo
Abstract: Ribosome engineering has been widely utilized for strain improvement, especially for the activation of bacterial secondary metabolism. This study assessed ribosome engineering technology to modulate primary metabolism, taking vitamin B12 production as a representative example. The introduction into Propionibacterium shermanii of mutations conferring resistance to rifampicin, gentamicin, and erythromycin, respectively, increased per cell production (μg/L/OD600 ) of vitamin B12 5.2-fold, although net production (μg/L) was unchanged, as the cell mass of the mutants was reduced. Real-time qPCR analysis demonstrated that the genes involved in vitamin B12 fermentation by P. shermanii were activated at the transcriptional level in the drug-resistant mutants, providing a mechanism for the higher yields of vitamin B12 by the mutants. These results demonstrate the efficacy of ribosome engineering for the production of not only secondary metabolites but of industrially important primary metabolites. Graphical abstract: : The introduction of drug resistance mutations into P. shermanii increased per cell production (μg/L/OD600 ) of vitamin B12 5.2-fold, although net